MODERN MINIMALLY INVASIVE SURGICAL TECHNIQUES AND FIXATION METHODS FOR LOWER JAW FRACTURES. - Jamoldinov Muhammadyusuf Jaloldin o’g’li; Tovasharov Muhammadali Yuldoshevich; Tohirjonov Azizbek Akmaljon o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores contemporary minimally invasive surgical techniques and fixation methods for managing lower jaw (mandibular) fractures. The discussion encompasses the advantages, challenges, and outcomes associated with these methods, backed by recent advancements in surgical tools and imaging technologies. The study also presents practical insights and recommendations for clinicians.